BRUTAL KILLINGS IN THE NAME OF HONOUR: IS HONOUR WORTHY THAN LIFE - Sharma, Gunjan; Kumar, Mandeep (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the culture of respect, the respect of the family depends on the behavior and sexuality of the girl or woman during her youth and therefore ensures that the rules are enforced. Deep dives into explaining what is and is not appropriate. Anyone who breaks these rules and regulations are punished, usually in the form of murder; "So-called" honor killing is promoted and practiced by the community because for them family honor means everything and worthy than life. Abuse and violence in the name of "so-called" respect prevents girls and women from choosing their own lives. This practice prevents them from living and enjoying their daily lives and is a form of bigotry and human rights violation. More research is needed in this area. The factors behind respect violence are traditional and cultural in society, but can be explained by economic and social problems. In a hostile economic environment, respect is a guarantee of family happiness. More in-depth research is needed to understand this relationship.